Integrating ecosystem services modeling and efficiencies in decision-support models conceptualization for watershed management - Pascual, Adrián; Giardina, Christian P.; Povak, Nicholas A.; Hessburg, Paul F.; Asner, Gregory P. (Ecological modelling, 2022)
Decision-making resource stewardship models rely on statistical relationships between management actions and ecosystem services provisioning. The operationalization of management actions benefits from models capable to isolate synergic statistical relationships from trade-offs. We showcase two existing watershed planning studies requiring spatiotemporal operationalization to better schedule management actions. The study in Hawai'i Island (USA) focused on invasive species while another in Babeldaob Island (Republic of Palau) tackled wildfire management. Both planning exercises relied on Ecosystem Management Decision Support to populate hydrologically defined management units for supporting water resource decision-making. In this viewpoint we identify shortcomings and potential future directions aligned with shaping stewardship responses to the interactive constraints of climate mitigation and management costs within a very needed optimization framework capable to operationally support landscape managers and drive solutions on ES management and valuation.